APPLICATION OF THE SHIRKAH 'ABDĀN CONTRACT IN THE MANAGEMENT OF GARDENIA AND SAIJO HOMESTAYS IN BINTANG ACEH TENGAH DISTRICT - Weta Rusma Rihlana; Abdullah, Arifin (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
The rapid growth of the tourism industry in Central Aceh, particularly in Bintang District, has stimulated the emergence of alternative accommodation businesses such as homestays. Homestay Gardenia and Saijo exemplify the application of the syirkah 'abdān partnership system, a cooperative arrangement in which the parties contribute labour and expertise ('amal) rather than financial (māl). This study aims to analyze the implementation of the syirkah 'abdān contract in the management of Homestay Gardenia and Saijo, focusing on the form of cooperation, the profit-sharing mechanism, and its conformity with Islamic economic law principles. Using a qualitative method with a normative-empirical approach, the data were collected through interviews with homestay owners and managers, supported by a review of relevant Fiqh literature and previous research. The findings indicate that the cooperation practices at Homestay Gardenia and Saijo resemble the syirkah 'abdān contracts, where both parties contribute their respective expertise and effort to achieve shared benefits. Although the agreements are valid in principle, the absence of written contracts poses potential risks of gharar (uncertainty) and unequal accountability. Therefore, formalizing the agreement in written form is recommended to ensure transparency, fairness, and compliance with sharia principles. Overall, the implementation of syirkah 'abdān in homestay management demonstrates the relevance of Islamic partnership ethics in fostering community-based tourism enterprises that promote justice, sustainability, and mutual prosperity.